2021
DOI: 10.1002/cpp.2632
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to combat incidents within military and civilian populations as possible correlates of potentially morally injurious events and moral injury outcomes among Israeli combat veterans

Abstract: Objectives: Exposure to potentially morally injurious events (PMIEs) is considered a necessary but insufficient determinant of moral injury (MI) outcomes. However, a question remains regarding possible acts and the necessary features of PMIEs that should be considered transgressive and might lead to MI psychopathological outcomes. We aim to examine the links between exposure to combat incidents within civilian Palestinian populations (CPPs), PMIEs and MI-related outcomes of posttraumatic stress disorder (PTSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 48 publications
3
33
1
Order By: Relevance
“…Studies focusing on this population are of particular value during the COVID-19 period. Indeed, several studies have shown that the COVID-19 pandemic crisis heightened PMIE exposure among HSCWs worldwide (Hines et al, 2020;Zerach & Levi-Belz, 2021). Moreover, PMIE exposure and MI symptoms among HSCW during the COVID-19 crisis has been linked to several mental health indicators, including secondary traumatic stress (Litam & Balkin, 2021), PTSD (Maftei & Holman, 2021), CPTSD (Zerach & Levi-Belz, 2021), depression, anxiety, and impaired well-being (Amsalem et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on this population are of particular value during the COVID-19 period. Indeed, several studies have shown that the COVID-19 pandemic crisis heightened PMIE exposure among HSCWs worldwide (Hines et al, 2020;Zerach & Levi-Belz, 2021). Moreover, PMIE exposure and MI symptoms among HSCW during the COVID-19 crisis has been linked to several mental health indicators, including secondary traumatic stress (Litam & Balkin, 2021), PTSD (Maftei & Holman, 2021), CPTSD (Zerach & Levi-Belz, 2021), depression, anxiety, and impaired well-being (Amsalem et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that the COVID-19 pandemic crisis heightened PMIE exposure among HSCWs worldwide (Hines et al, 2020;Zerach & Levi-Belz, 2021). Moreover, PMIE exposure and MI symptoms among HSCW during the COVID-19 crisis has been linked to several mental health indicators, including secondary traumatic stress (Litam & Balkin, 2021), PTSD (Maftei & Holman, 2021), CPTSD (Zerach & Levi-Belz, 2021), depression, anxiety, and impaired well-being (Amsalem et al, 2021). Following these findings, it is essential to extend our theoretical understanding and clinical practices as well as explore potential risk conditions and protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of combat-related PTSD is estimated at 6–25% and is dependent on the intensity of combat exposure and differences in war theaters and eras (e.g., Fulton et al, 2015). Specifically, recent studies have reported about 21% of Israeli Defense Forces (IDF) combat veterans—the target population of this study—cope with self-reported probable PTSD following military combat service (Zerach & Levi-Belz, 2021,Zerach & Levi-Belz, 2021). Many veterans may also experience a symptom intensity range below the threshold required to establish a diagnosis, although still experiencing PTSS.…”
Section: Introductionmentioning
confidence: 99%
“…Moral injury occurs as a result of a potentially morally injurious event (PMIE) (Phoenix Australia, 2020). Examples of a PMIE include; not being able to intervene to protect civilians because of the rules of engagement, having to make decisions that affect the survival of others, or the harming or killing others in the context of war Zerach & Levi-Belz, 2021). In these instances, the thoughts and feelings associated with the PMIE event can mediate the relationship between being exposed to a violent situation and guilt and shame (Zerach & Levi-Belz, 2021).…”
Section: Moral Injurymentioning
confidence: 99%
“…Examples of a PMIE include; not being able to intervene to protect civilians because of the rules of engagement, having to make decisions that affect the survival of others, or the harming or killing others in the context of war Zerach & Levi-Belz, 2021). In these instances, the thoughts and feelings associated with the PMIE event can mediate the relationship between being exposed to a violent situation and guilt and shame (Zerach & Levi-Belz, 2021). This means that the way that the individual interprets the morally injurious event can influence whether they experience adverse outcomes, such as feelings of guilt and shame.…”
Section: Moral Injurymentioning
confidence: 99%